DIVERSITY OF TREE SPECIES IN SYIAH KUALA UNIVERSITY - Djufri Djufri; Hasanuddin Hasanuddin; Abdullah Abdullah; Vivera Ruselli Puspa (BIOTIK: Jurnal Ilmiah Biologi Teknologi dan Kependidikan, 2022)
This research was conducted from April 2020 to October 2020 entitled "Diversity of Tree Species at Syiah Kuala University". The data collection technique was performed through a survey of 21 observation plots including faculties, office units, worship facilities, health facilities and other supporting facilities. The data analysis includes the Important Value (NP) and Species Diversity Index (H'). The results showed that the species composition of trees growing on the campus of Syiah Kuala University were 46 species belonging to 27 families. Six tree species that had relatively high importance value compared to others, namely Pterocarpus indicus (19.61%), Swietenia mahagoni (19.56%), Polyathia longifolia (12.76%), Mimusops elengi (12.48%), Roystonia regia (12.27%), and Samanea saman (10.176%). The Diversity Index (H') of those tree species ranged from 1.549 to 2.634. The conclusion is that the tree species composition was relatively limited when compared to the Cronquist classification, and the tree species diversity index was in the medium category.